2013
DOI: 10.1111/jfbc.12034
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Antioxidant Potency and Antibacterial Activity of Water Extracts of Some Spices Widely Consumed in Iranian Diet

Abstract: The present study was conducted to evaluate the antioxidant and antibacterial activities of water extracts of sumac (Rhus coriaria), barberry (Berberis vulgaris), black pepper (Piper nigrum), red pepper (Capsicum annuum), fennel (Foeniculum vulgare), laurel (Laurus nobilis), cardamom (Elettaria cardamomum), turmeric (Curcuma longa), white mustard (Sinapis alba) and nutmeg (Myristica fragrans). The antioxidant activity of extracts was tested using 2,2-diphenyl-1-picrylhydrazyl and reducing power tests. The anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…In addition, there are growing concerns among people about the safety of foods containing synthetic chemicals. Therefore, exploring natural food preservatives with antioxidant and antibacterial effects has attracted increasing interest for both food industry and scientists (Aliakbarlu et al, 2014;Shan, Cai, Brooks, & Corke, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are growing concerns among people about the safety of foods containing synthetic chemicals. Therefore, exploring natural food preservatives with antioxidant and antibacterial effects has attracted increasing interest for both food industry and scientists (Aliakbarlu et al, 2014;Shan, Cai, Brooks, & Corke, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid oxidation and foodborne pathogenic bacteria growth in foods are two major causes of food spoilage (Aliakbarlu, Mohammadi, & Khalili, 2014), which can lead to food poisoning. In order to inhibit lipid oxidation and bacterial growth in foods, many synthetic food preservatives are widely used in raw and processed food (Frankel, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Different beneficial compounds are found in all parts of plants such as leaves, fruits, seeds, roots and bark; several elements of this chemical mixture may possibly be found advantageous with their biological activities such as antioxidant activity (AA) (Aliakbarlu et al . .…”
Section: Introductionmentioning
confidence: 99%
“…In mature stage the phenols content ranged from 648.6 mg chlorogenic acid equivalent/100g FW for Acuminatum cultivar to 679.6 mg/100 g FW chlorogenic acid equivalent for Orange Thai cultivar. Aliakbarlu et al [32] found that TPC in red pepper was 34 mg GAE/g DW. Chen and Kang [33] observed that TPC of red peppers in pericarp, placenta and stalk were ranged from 43.3 to 91.9 mg GAE/g DW.…”
Section: Polyphenols Contents and Antioxidant Activitiesmentioning
confidence: 99%